The Existence of Strong Solutions for a Class of Stochastic Differential Equations - Junfei Zhang (International Journal of Differential Equations)
In this paper, we will consider the existence of a strong solution for stochastic differential equations with discontinuous drift coefficients. More precisely, we study a class of stochastic differential equations when the drift coefficients are an increasing function instead of Lipschitz continuous or continuous. The main tools of this paper are the lower solutions and upper solutions of stochastic differential equations.